8×8 Wheeled Vehicle Modeling in a Multibody Dynamics Simulation Software. (2015) - Gorelov, V.A.; Komissarov, A.I.; Miroshnichenko, A.V.
Abstract: The article describes a three-dimensional non-linear dynamic model of a 8×8 wheeled vehicle. The authors used the "Universal Mechanism" MBS software to build the model. The article also presents a tire – rigid terrain interaction model built in Matlab/Simulink. The authors tested the process of linking a Matlab/Simulink DLL to the vehicle MBS model. The authors used the developed model to analyze the wheeled vehicle dynamic behavior at different operation conditions. The article contains the results of the lane change test simulation. The simulation results confirmed the validity of the model. The developed model allows the estimation of the wheeled vehicle dynamic behavior at various operation conditions at the design stage.